P 59 Interplay of the cellular actions of neuropeptide Y and transcranial magnetic theta-burst stimulation on cortical inhibitory systems – a rat study. Issue 10 (October 2017) - Jazmati, D.; Neubacher, U.; Aliane, V.; Funke, K.
Abstract : Questions: Our previous studies showed that intermittent theta-burst stimulation (iTBS) applied via transcranial magnetic stimulation (TMS) to the rat brain strongly reduced the expression of the calcium-binding protein parvalbumin (PV) in fast-spiking inhibitory interneurons (FSI). This finding indicates that disinhibition and the associated increase in cortical excitability may be one way to open a window for plastic changes in the cortical network. The mechanisms leading to reduced PV expression are not known but are either related to a strong activation during iTBS or a subsequent reduction in glutamatergic excitation of FSI in a manner of Ltd. One well-described regulator of glutamate release at excitatory terminals is neuropeptide Y (NPY) which has been shown to be up-regulated after epileptic activity. Therefore, we tested if iTBS increases the expression of NPY in rat cortex, whether the reduced PV expression in FSI is associated with reduced activity of excitatory inputs and finally if intrathecal application of NPY prior to TMS can counteract the cortical iTBS effect. Methods: In a first study, parallel changes in the cortical expression of PV and NPY in rats previously treated with one to five blocks of iTBS (600 pulses per block, intervals of 15 min) were analysed using immunohistochemistry. In a second study, we analysed the relationship between the level of PV expression of single FSI and the strength of glutamatergic input measured as the level of expression of the vesicular glutamate transporter type 1 (VGluT1) in cortical synapses terminating on FSI. Finally in a third study, rats received either 20 μ l NPY (24 nMol) or methylene blue as a control (MB) via intracranial injection to the left lateral ventricle (2 μ l/min) followed 60 min later by either verum or sham iTBS (3 blocks @ 15 min = 1800 pulses) to test if enhanced NPY level can influence the effect of iTBS on PV and vGluT1 expression. Results: In a dose-dependent fashion, iTBS gradually decreased the number of PV+ neurons but also increased the level of NPY in the neuropil and the number of NPY+ neurons. Interneurons showing low PV expression had a significantly weaker labelling of glutamatergic cortical input (less vGluT1) than cells showing high PV level. NPY injected into the lateral ventricle of the left forebrain (no diffusion to the right hemisphere) prevented the reduction of PV+ cells (−40%) by iTBS in the left but not in the right hemisphere and further increased the number of PV+ cells. A slight increase in PV+ cells was also evident in sham stimulated animals when comparing NPY with MB injections. Conclusions: As expected, iTBS increased the expression of NPY likely due to the strong and highly synchronous activation of cortical networks. Since strong excitation is especially harmful to FSI, the reduction in PV expression appears to signal a post-stimulation depression of excitatory inputs and subsequent hypoactivity of these interneurons. The finding that NPY prevents the strong reduction in PV expression indicates that it is able to prevent over-excitation of FSI. This study has been supported a grant of theFederal Ministry of Education and Research (BMBF): GCBS-WP1_Bochum (01EE1403B ) to K. Funke.